Perancangan Sistem Informasi Administrasi Pembayaran SPP Siswa Berbasis Web - yusran, yusran (STKIP PGRI Sumatera Barat, 2020)
The development of technology and the development of science triggered many people to look for alternative solutions to problems in the field of information systems technology. Information technology is currently a very important requirement for the organization or company. Information technology has been widely used for various aspects such as management and human resources. Tuition payments are needed by madrasas to support educational needs, the current system is still done manually, madrasah treasurers record students who will pay tuition fees in books. Therefore researchers use the design of the MA Baiturrahaman SPP payment application to support the performance of the madrasa treasurer to conduct transactions quickly, and do not need to multiply work to process transactions and SPP payment report. The SPP payment application is designed with several stages ranging from data collection to system testing. The application design is designed using UML and developed with the java programming language and MariaDB as a database. The results of this study the treasurer can easily make payment transactions and SPP payment reports can be resolved properly.